Numerical simulations for the fluid-thermal-structural interaction lubrication in a tilting pad thrust bearing. Issue 4 (12th June 2017) - Zhai, Liming; Luo, Yongyao; Liu, Xin; Chen, Funan; Xiao, Yexiang; Wang, Zhengwei
Abstract : Purpose: The purpose of this paper is to analyze lubrication characteristics of a tilting pad thrust bearing considering the effect of the thermal elastic deformation of the pad and collar. Design/methodology/approach: This study used the fluid–solid interaction (FSI) technique to investigate the lubrication characteristics of a tilting pad thrust bearing for several typical operating conditions. The influences of the rotational speed, the thrust load and the oil supply temperature on the lubrication characteristics were analyzed. Findings: The three-dimensional (3D) film model clearly shows that there is no pressure gradient but large temperature gradients across the film thickness. The wall heat transfer coefficients on the pad surfaces distribute in a very complex way and change within a large range. The rotational speed, the thrust load and the oil supply temperature have great but different influences on the lubrication characteristics. Originality/value: This paper has preliminarily revealed the lubrication mechanism of the tilting-pad thrust bearings. The 3D FSI method is suggested to evaluate the thermal-elastic-hydrodynamic deformations of thrust bearings instead of the conventional method which iteratively solves the Reynolds equation, the energy equation, the heat conduction equation and the elastic equilibrium equation. Using FSI method, the heat transfer coefficients on the pad surfaces can be evaluated better.